ANALISIS TINGKAT KESULITAN MAHASISWA PROGRAM STUDI PENJASKESREK UNIVERSITAS RIAU ANGKATAN TAHUN 2017 DALAM MENYELESASIKAN PENYUSUNAN TUGAS AKHIR - Neldi, Novielsa Rika Putri; Juita, Ardiah; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The thesis is a very important aspect. This work is not only a marker ofsomeone's eligibility to obtain a bachelor's degree. To complete a thesis, students must go through a long process that galvanizes them in various aspects, both intellectual, mental, social and spiritual. During this process, many things will shape and perfect the students' personal qualities, so that they deserve to be called graduates. In reality, many students experience difficulties in completing their theses, which often results in completing their studies beyond the normal time limit for obtaining a bachelor's degree, which is more than four years. This research problem was caused by several factors, one of which was feeling lazy about doing the final assignment, lack of communication with the relevant lecturer, and fear of meeting the relevant lecturer about completing the final assignment. This type of research is included in research with a qualitative approach, because the form of data is in the form of verbal and descriptive information about an object being studied. Presentation of qualitative data is usually conveyed in the form of descriptions, explanations and interpretations of a phenomenon that is the object of research. This research is also descriptive research carried out to describe or describe the research object in its actual situation without any intention of drawing conclusions. The results of the research revealed that the constraint indicator for final year students had an achievement indicator of 66.14% in the good category, while the development indicator for final year students had an achievement indicator of 68.74% in the good category. The average achievement of each indicator is 67.44%, which explains that the difficulties of students in the Physical Education study program at the University of Riau Class of 2017 in completing their thesis are in the good category.Key Words: Student, Physical Education, Final Project, University of Riau.